Challenges in Speaking Skill Faced by EFL Learner in Lombok Timur - Rizkon, Miftahul; Sukmawati, Lisa; Ratna, Nagita; Misouwarini, Nur; Nurpazila, Nurpazila; Riadi Jaelani, Selamet (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
The aim of this study is to know the challenges that faced by EFL learner. To achieve this objective, descriptive research was implemented. Furthermore, the subject in this researcher was 24 EFL learners in Lombok Timur. Technique of data collection were questionnaire and interview. As a result of students’ responses, there are three challenges faced by EFL learners in Lombok Timur. They are lack of vocabulary (58,3%), lack of confidence (20,8%) and no partners to speak English with (20,8%).